Geodis Malaysia Sdn. Bhd. / Nurjanah Nazri - Nazri, Nurjanah (Faculty of Business and Management, 2023)
According to the plan of study, internship is the last course for all undergraduate program in the Faculty of Business and Management. A student is required to undergo internship attachment or on-the-job training in areas related to our academic degree and field of concentration. This internship course serves as a practical training ground for a student to receive practical knowledge and workplace skills that give experience with work and responsibility in carrying out tasks. The objective of this research is to provide an overview of Geodis Malaysia Sdn Bhd's SWOT analysis as well as organization. The SWOT analysis was performed to identify the company's opportunities, and threats. The findings of the analysis will be used to create a strategy plan for the organization strengths, weaknesses,